STEREOLOGY OF NANO-MATERIALS - Wejrzanowski, Tomasz; Lewandowska, Małgorzata; Kurzydłowski, Krzysztof J (Image Analysis and Stereology, 2011)
Nano-structured materials attract a growing attention due to their superior mechanical and physical properties. Such properties are inherently related to the unique structure which is controlled at the nano-scale. In the early stage of their development, the structural characterization of nano-materials was limited to the average grain/particle size. However, nano-grains/particles form stochastic populations with diverse size and shape. The recent experimental and theoretical results show that in addition to the average size, size diversity of grains/particles has a significant effect on the properties of nano-materials. This rationalizes more advanced description of the structures of nano-materials. Advanced microscopic methods are now available to image microstructure of nano-materials, e.g., HRSTEM and AFM. The ultra-high resolution images can be efficiently processed to obtain quantitative description of the nano-grains/particles. Examples are shown how such a description can be used for optimizing the microstructures of modern engineering nano-materials.